Evaluasi Pencatatan Pendapatan Atas Penerimaan Premi, Pembayaran Tabungan Hari Tua (Tht) Dan Pensiun Serta Pertanggungjawaban Kepada Kas Negara Studi Kasus Pada PT Taspen (Persero) Cabang Bogor - Rosita, Siti Ita (Jurnal Ilmiah Kesatuan (JIK), 2010)
PT Taspen (Persero) is a state company managing savings and insurance funds of government employees. The participants of those programs are the retired civil public servants (PNS). Considering how important the pension fundsfor supporting their old days life, PT Taspen (Persero) has made old age savings (THT, including mortality insurance), pension (including donation for mourners), welfare program for civil public servants(PNS), and other social security programs. The revenue gotten by PT Taspen (Persero) is the premium income of old savings and pensions. Premium income is PT Taspensâ revenue obtained fromsalaries witholding of PNS or states officials as high as 4,75% of their main salary and wife-dependantâs allowance. Whereas, premium revenue of THT is salaries witholding of PNS as high as 3,75% of their main salary and wifi-dependantâs allowance. PT Taspen will bring about payment of pension and THT funds to the participants who have the right to receive their money. PT Taspen reimburses pension in cash and by transferring via bank. PT Taspen will submit pension fund to the given office of the bank determined, after that it will be submitted to the participants. PT Taspen will make letter of pension reimbursement accountability (SPJP) after receiving accountability report from the treasurer of payment office. The SPJP must be legalized first by KPPN, then itâs submitted to PT Taspenâs center office.